Neopolitan Psychiatric Health Resort advancing wellness through salutogenic and evidence-based design - Belmonte, Eugene Fernando F.; Rinen, Richard Martin E. (Quezon City College of Architecture, University of the Philippines Diliman, 2017)
The creation of the project was in response to the growing mental health problem of the country, particularly Metro Manila. The Neopolitan Psychiatric Health Resort is an addition to the limited number of hospital beds dedicated for psychiatric health. The design of the facility replicateds the paradigm of salutogenesis and evidence-based design, both of which has integral part in the health and recovery of the patients. The facility is a 207-bed psychiatric hospital servicing both outpatients and inpatients. The outpatient department is subdivided into four- Psychological Services, Mental Health Clinic, Substance Abuse Clinic, and Psychosocial Services. The inpatient department houses single-bed rooms as part of the program of the hospital, with resort facilities in support with their fast recovery. For long term patients, the Residential Rehabilitation Program house patients in 15 four-bed residential units, with their own common facilities. With the adaptation of the agenda-based design methodology of this architectural thesis, the process begins with the identification of the agenda from the site analyzed, and the architectural solutions were derived from existing body of knowledge, in this case evidence-based design and salutogenesis, which are the precedents in coming up with the final design of the project.
Thesis (Bachelor of Science in Architecture) -- University of the Philippines Diliman
Keywords: Neopolitan Psychiatric Health Resort